(untitled) - Allaby, Michael (Oxford, UK, 1994)
The Concise Oxford Dictionary of Ecology provides 5,000 up-to-date entries on all aspects of ecology and the environmental sciences. With many entries derived from the acclaimed Oxford Dictionary of Natural History, it covers a vast range of subjects, from plant and animal physiology, animal behavior, evolution, environmental pollution, and conservation to climatology, meteorology, geomorphology, and oceanography. Also included are biographical notes on eminent ecologists and other scientists, as well as helpful cross-references that make this volume an invaluable reference tool for students, professionals, and anyone with an interest in the natural world and our environment
Keywords: Ecology,Environmental sciences